Interdepartmental coordination experience and collaborative learning applied to Bachelor Final Project (2012-2017) - P.J. Martín Castejón; M. Lafuente-Lechuga; U. Faura-Martínez; M.C. Puigcerver Peñalver; M. Bote (Universitat Politècnica de València, 2018)
It is unusual to find collaborative learning experiences in higher education, even more rare is the use of this pedagogic tool in the development of the Bachelor Final Project. This work shows the implementation and results of an innovative teaching Project based on horizontal coordination between several departments (Marketing and Quantitative Methods) together with collaborative learning in the Bachelor Degree in Business Management and the Bachelor Degree in Marketing in the School of Economics of University of Murcia (southeast Spain). In order to implement the Project, a transversal topic was created ("Entrepreneurship and business projects") based on the development of a business plan through a calendar of on-campus mentoring and collaborative learning between the students. Academic results reveal a significant improvement in the final marks of students when compared with students working on other topics, being marks on average up to one point higher. Finally, advice and tips are provided to better-applied collaborative learning in similar experiences in the higher education setting, taking into account some problems which emerged during the design and implementation of this teaching project.